Block-based physical modeling with applications in musical acoustics - Rabenstein, Rudolf; Petrausch, Stefan (Zielona Góra: Uniwersytet Zielonogórski)
Block-based physical modeling is a methodology for modeling physical systems with different subsystems. Each subsystem may be modeled according to a different paradigm. Connecting systems of diverse nature in the discrete-time domain requires a unified interconnection strategy. Such a strategy is provided by the well-known wave digital principle, which had been introduced initially for the design of digital filters.
Keywords: physical modeling; wave digital filters; sound synthesis